Is the atrial fibrillation anticoagulation bridge falling down?. Issue 11 (November 2015) - Jarrett, Jennie Broders; Schaffer, Ted
Abstract : N/A: Douketis JD, Spyropoulos AC, Kaatz S, et al. Perioperative bridging anticoagulation in patients with atrial fibrillation. N Engl J Med . 2015; 373(9):823–833.